Enhancing climate adaptation planning with limited resources: A streamlined framework for municipal climate risk assessments - Nicolas Hübner; Matthias Finkbeiner (Climate Risk Management, 2025)
Municipalities are key actors in climate adaptation, facing unique vulnerabilities and specific local climate risks. Yet, municipal adaptation planning often remains reactive and incremental, lacking the strategic foundation for long-term resilience.Local Climate Risk Assessments (CRAs) are critical for identifying and prioritizing adaptation needs, and allocating resources effectively, but their technical complexity and resource demands pose challenges, particularly for municipalities with limited capacities.We present the “Streamlined Municipal Adaptation Risk Tool for Climate Risk Assessments” (SMART-CRA), a decision-centric framework that operationalizes and adapts the general CRA process of ISO 14091 for municipal contexts. It introduces a heuristic comparative reference approach that builds on an existing national CRA to reduce technical effort while maintaining scientific rigor. This shifts the focus toward participatory evaluations and increases local relevance.Applied in the German municipality of Geestland, SMART-CRA identified high-priority climate risks across relevant sectors within six months, coordinated by a single key person responsible for managing data collection and stakeholder engagement, demonstrating its feasibility in resource-constrained settings. While designed for broad applicability, successful implementation depends on enabling factors, such as access to high-resolution data, a robust reference CRA, and dedicated personnel, e.g., a climate adaptation manager, which may be less available in developing contexts. Key challenges relate to the inherent limitations of the comparative reference approach, the subjectivity of normative evaluations, and uncertainties in climate projections. To avoid maladaptation and account for uncertainty, contextual judgment and continuous refinement of adaptation strategies over time remain essential.